Flexible outsourcing and the impacts of labour taxation in European welfare states - Koskela, Erkki; Poutvaara, Panu (Munich, 2008)
"In European Welfare States, low-skilled workers are typically unionized, while the wage formation of high-skilled workers is more competitive. To focus on this aspect, we analyze how flexible international outsourcing and labour taxation affect wage formation, employment and welfare in dual domestic labour markets. Higher productivity of outsourcing, lower cost of outsourcing and lower factor price of outsourcing increase wage dispersion between the high-skilled and low-skilled workers. Increasing wage tax progression of lowskilled workers decreases the wage rate and increases the labour demand of low-skilled workers. It decreases the welfare of low-skilled workers and increases both the welfare of high-skilled workers and the profit of firms."